Deux lacs à problèmes du Centre-Var : le Grand Loucien de La Roquebrussanne et le Lac de Besse-sur-Issole - Jean Nicod (Physio-Géo)
The little lakes of Middle Var Department are located in karstic depressions produced by solution of gypsum or anhydrite in the triassic formations. Their new evolution show main typical, hydrological and environmental problems.